Law and sociology - Freeman, Michael D. A. (Oxford : Oxford University Press, 2006)
'Law and Sociology' contains a broad range of essays by scholars interested in the interactions between law and sociology.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Sociological jurisprudence